Keberhasilan Mendeteksi Gen Penyandi Resistensi Tetracycline dan Plasmid Mediated Quinolones pada Bakteri Salmonella Ayam di Bandung dan Purwakarta - Aziah, Leila Nur; Indrawati, Agustin; Wibawan, I Wayan Teguh (Jurnal Veteriner, 2020)
This study was aimed to identify genes encoding tetracycline and plasmid-mediated quinolones resistance to Salmonella spp from Poultry Farm in Bandung and Purwakarta, West Java. A total of 70 samples were collected from poultry farm in Bandung and Purwakarta, West Java. All isolates were test by selective media (Salmonella Shigella Agar/SSA) and confirmation Salmonella with polymerase chain reaction (PCR). Thirty three isolate positive from selective media Salmonella Shigella Agar (SSA) and 21 isolat was confirmed as Salmonella spp by PCR. A total of twenty one isolate isolated were tested for tetracycline, doxycicline,, nalidixic acid, oxytetracycline, enrofloxacyn using disk diffusion method. TEresistant were screened for presence of tet(A) and tet(B) genes by single PCR. The qnr(A), qnr(B) and qnr(S) genes were detected by multiplex PCR in quinolone resistant Salmonella isolates. The result of antibiotic sensitivity test showed that resistance to ampicillin (95.2%), tetracycline (100%), oxytetracycline (95.2%), nalidixic acid (90.4%), eritromisin (85.7%), enrofloxacin (76.2%), Gentamisin 47.6%, chloramphenicol (38.1%). The distribution of antibiotics-resistance genes in the Salmonella isolates included ampC (95.2%), tet(A)(61.9%), tet(B)(38.1%), qnr(A)(28.5%), qnr(B)(14.3%) and qnr(S)(23.8%). This study shows that a few pathogens of Salmonella are resistant to ampicillin, tetracycline , and quinolone. The tet and qnr genes are responsible for this resistance among Salmonella in Bandung and Purwakarta, West Java Indonesia was high.